Poluentes atmosféricos: monóxido e dióxido de carbono no nordeste do Brasil - Pereira, Cleuber Dias (2011)
The interference of man in the middle atmosphere can be evidenced by the presence of carbon monoxide, gas associated with burning fossil fuels and carbon dioxide content, essential for respiration of plants and thermal balance of the Earth. In this thesis we initially evaluated the intensity of the spatial distribution of carbon monoxide in the Northeast of Brazil, and subsequently the behavior of temporal variations of the pollutants carbon monoxide and carbon dioxide in the atmospheric boundary layer Maxaranguape / RN. Research has shown that, driven by speculation and promoting the occupation of land for agriculture, cattle ranching and tourism in the Northeast of Brazil, the changes established by the man in the middle geomorphological affect the lower troposphere on a large scale, with a predominance of concentrations in central Pernambuco, Paraiba's south-central and central-west of Alagoas. However, the study of Maxaranguape / RN results showed little variation in carbon monoxide and carbon dioxide, with the speed of the wind persisting with values greater than 7.8 m / s, showing dispersion and diffusion of pollutants which resulted in faster renewal of local atmospheric air